Elucidating the heterogeneity of endometriosis using multi-omics - Cheuk, SKC (2020)
Endometriosis is a common chronic inflammatory gynaecological condition associated with a spectrum of clinical presentations including different types of pelvic pain and infertility. It is defined as the presence of endometrial-like tissue outside the uterus. Diagnosis requires invasive surgery, resulting in a typical diagnostic delay of 7-10 years, whilst treatment options are limited to repeated surgeries or hormonal medication. Although the disease has a moderate (50%) heritability, the genetic and epigenetic causes of the disease are largely unknown; where genetic variants have been identified, the biological pathways that are perturbed remains unknown. Despite the evidence that endometriosis is a clinically and aetiologically heterogeneous condition, most studies to date are studying endometriosis as binary condition, without regard for the wide spectrum of sub-phenotypes that patients are experiencing. Understanding biological differences between sub-phenotypes of endometriosis, both surgical and symptomatic, is important for the development of better targeted treatment methods as well as non-invasive methods of diagnosis. This thesis aims to examine for the first time differences in genomic, transcriptomic, and epigenomic characteristics of different sub-phenotypes of endometriosis, to aid understanding of their pathogenesis.